The "classification-strategies" method for the eco-transition of "mine-city" system-taking Xuzhou city as an example - Pingjia Luo; Yankai Miao; Jiang Chang (Journal of Urban Management, 2020)
The transition of coal-exhausted city (CEC) has been a worldwide problem, the transition planning of the CEC is a synergetic procedure. When we look into the transition problem of a larger CEC, the difficulties for the city planner come from the synchronicity, otherness and complexity of the "Mine-City" system. Xuzhou City is the largest CEC in the world and has the most complex "Mine-City system". The researches on the transition of Xuzhou would be a good example to the complex "Mine-City" system planning in the world. The bio-city is the best transition target for Xuzhou city. Based on this understanding, a "Classification-Strategy" method for Xuzhou city's eco-transition is proposed. The "Mine-City" system of Xuzhou is classified into 3 basic types: urban type, rural type and suburban type. The corresponding practical strategies are proposed. The "Classification-Strategy" method has the advantages of simple and practical, and can give the city planner a more comprehensive consideration of the planning elements during the eco-transition of the "Mine-City" system.
Keywords: 710; Classification-strategies; Eco-transition; Mine-city system; Resource-exhaustedcity; Symbiotic system